2003
DOI: 10.1038/nature01778
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoceanographic implications of genetic variation in living North Atlantic Neogloboquadrina pachyderma

Abstract: The shells of the planktonic foraminifer Neogloboquadrina pachyderma have become a classical tool for reconstructing glacial-interglacial climate conditions in the North Atlantic Ocean. Palaeoceanographers utilize its left- and right-coiling variants, which exhibit a distinctive reciprocal temperature and water mass related shift in faunal abundance both at present and in late Quaternary sediments. Recently discovered cryptic genetic diversity in planktonic foraminifers now poses significant questions for thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 27 publications
5
49
0
3
Order By: Relevance
“…genotypes were identified by Darling et al (2004) in the Arctic and Antarctic polar/subpolar waters. Those cryptic species seem to have different environmental preferences (Bauch et al, 2003). Accordingly, the temperature tolerance of the populations in the southern hemisphere is larger than that of North Atlantic population (Darling et al, 2006).…”
Section: Comparison With Core-top Datamentioning
confidence: 99%
See 1 more Smart Citation
“…genotypes were identified by Darling et al (2004) in the Arctic and Antarctic polar/subpolar waters. Those cryptic species seem to have different environmental preferences (Bauch et al, 2003). Accordingly, the temperature tolerance of the populations in the southern hemisphere is larger than that of North Atlantic population (Darling et al, 2006).…”
Section: Comparison With Core-top Datamentioning
confidence: 99%
“…N. pachyderma (sin.) is a cold-water species, and dominates planktonic foraminiferal assemblages in polar waters (Pflaumann et al, 1996;Bauch et al, 2003;Kucera et al, 2005). Previous work has shown that it can survive within Antarctic sea ice (Dieckman et al, 1991;Spindler, 1996;Schnack-Schiel et al, 2001).…”
Section: Spatial Distribution Patternsmentioning
confidence: 99%
“…However, the discrimination between the N. incompta and N. pachyderma (d) can be achieved only by means of genetic analysis and is not possible for fossil material. Data from Bauch et al (6) suggest that the d show 0.5‰ enrichment before HE1, not 3‰ as reported by Hillaire-Marcel and de Vernal (2).…”
mentioning
confidence: 49%
“…crude parametrizations, or the complete lack of climate components) (Stainforth et al 2007) and proxy 'biases' (e.g. habitat variability or physiological plasticity) (Bauch et al 2003;Skinner & Elderfield 2005). Both of these types of uncertainty bear on the perils of extrapolation, and neither is easily quantified, let alone explicitly characterized.…”
Section: Looking Forward In Palaeoclimate Researchmentioning
confidence: 99%